Patrones estacionales del turismo de cruceros en España - Fernández-Morales, Antonio; Mayorga-Toledano, María Cruz (My University, 2015)
The aim of this paper is to present the first results of an exploratory investigation of the seasonal distribution of cruise tourism in Spanish ports. The methodology used in the study consists of a combination of factor and cluster analysis, in order to identify the regularities on the monthly distributions of cruise passengers that allow a classification of group into clusters with homogenous seasonal distributions. With statistical data of the last five years, the analysis yields some remarkable results. The clusters with the most homogeneous compositions are the Canary Islands ports and a cluster with the most mature ports in the Mediterranean Sea. In contrast, other clusters have been found with instable compositions along the observed period. Moreover, the former, with winter or summer bimodal seasonal distributions show lower Gini indexes than the latter, whose seasonal distributions are mainly unimodal
Keywords: Turismo cultural; Gini; Estacionalidad; Turismo de cruceros; Multivariante